Oseltamivir Monotherapy Compared with Combination Therapy Including Oseltamivir for Influenza – A Systematic Review - Bender, Aleksandra; Widomska, Katarzyna; Bernad, Mateusz; Walczak, Paulina; Szymulewicz, Bartłomiej; Łukaszewicz, Jakub; Gałach, Magdalena; Dąbrowski, Kacper; Niewęgłowska, Małgorzata; Krazińska, Oliwia (Journal of Education, Health and Sport, 2026)
Background. Influenza is considered by scientists and practicing physicians as a significant health problem, often leading to a variety of complications. One of the most commonly used treatments for influenza is oseltamivir. However, due to constantly changing influenza virus serotypes, oseltamivir treatment is sometimes insufficient. Therefore, researchers are investigating for new, more effective therapeutic approaches. Aim. The aim of this study was to determine whether a combination therapy including oseltamivir is more effective than monotherapy. Material and methods. We screened original articles evaluating virological and clinical outcomes of oseltamivir combination therapy, as well as publications investigating treatment with higher doses of oseltamivir. Data were collected from PubMed, Web of Science and Google Scholar. We defined the study population as adults with symptomatic and laboratory-confirmed influenza. Results. Finally, nine articles were included in the analysis, involving altogether 2,068 participants. In six of nine articles some improvement in viral load and/or symptoms duration was observed. Conclusions. Our findings suggest evidence supporting the effectiveness of a combination therapy – oseltamivir combined with pimodivir, favipiravir, azithromycin, ribavirin and amantadine or clarithromycin and naproxen. These medicines may have potential clinical applications, however, further research involving larger patient population is required.